Asymmetric information, disagreement, and the valuation of debt and equity - Banerjee, Snehal; Breon-Drish, Bradyn; Smith, Kevin (Journal of Financial Economics, 2025)
We study debt and equity valuation when investors have private information and may exhibit differences of opinion. Our model generates several predictions that are consistent with empirical evidence but difficult to reconcile with traditional models. Belief dispersion relates to expected equity and debt returns in opposite directions. Similarly, expected debt (equity) returns typically increase (decrease) with default risk, though these relationships reverse for firms close to bankruptcy. Firms’ capital structures affect their valuations even without classical capital structure frictions (e.g., tax shields, distress costs) – when liquidity is higher in the equity than in the debt market, leverage can raise firm value.